Intelligent Information Processing VIII 9th IFIP TC 12 International Conference, IIP 2016, Melbourne, VIC, Australia, November 18-21, 2016, Proceedings - Shi, Zhongzhi; Vadera, Sunil; Li, Gang (IFIP Advances in Information and Communication Technology,, 2016)
This book constitutes the refereed proceedings of the 9th IFIP TC 12 International Conference on Intelligent Information Processing, IIP 2016, held in Melbourne, VIC, Australia, in October 2016. The 24 full papers and 3 short papers presented were carefully reviewed and selected from more than 40 submissions. They are organized in topical sections on machine learning, data mining, deep learning, social computing, semantic web and text processing, image understanding, and brain-machine collaboration.